The effect of corporate governance attributes on human capital disclosure in South Africa - Magau, Mpho Dennis (Universitas Bangka Belitung, 2024)
The disclosure of human capital (HC) information in corporate reports continues to be at the centre of discussions in the executive boardroom. Currently, standard setters grapple with implementing uniform disclosure requirements for human capital disclosure (HCD) and as a result this information is scant, erratic, and inconsistently reported. Hence the ISO 30414 was introduced to breach this gap. The aim of the study is to critically examine how corporate governance attributes affect HCD. A quantitative based cross-sectional design was followed using a sample of top 100 companies listed on the Johannesburg Stock Exchange (JSE). The ISO 30414 HR reporting framework containing 48 metrics was utilised to construct an assessment instrument with a 7-point scale to assess the extent of HCD. Overall, board meeting attendance yielded positive statistically significant association with HC information disclosed on recruitment, retention rate, turnover rate, internal mobility rate, competency rate, employee value-added, absenteeism rate. The board of directors play a critical role in improving the disclosure of HC information in the integrated reports. The study provides first empirical evidence on the impact corporate governance attributes have on HCD using the ISO 30414 HR reporting framework.